My grief handbook why grief hurts and how to cope - Trickey, David; Clark-Tate, Olivia; Ferrari, Beck; Ravasio, Roberta (London Philadelphia Jessica Kingsley Publishers, 2024)
"In confronting bereavement head-on, Trickey and Ferrari have created a supportive and encouraging handbook that explains grief theories to children in an accessible way. Based on research and lived experience, it acknowledges the unique circumstances of every child, so that all can find advice that is meaningful and helpful"--
Includes bibliographical references.
Keywords: Grief in children -- Juvenile literature; Bereavement in children -- Juvenile literature